THE ACCURACY OF IDIOMS TRANSLATION FROM ENGLISH INTO INDONESIAN IN THE “TANGLED” FILM - Indra R. Ohorella; Silvani Umar Ali; Samsudin Hi. Adam (FKIP Universitas Khairun, 2021)
The study aims to analyze the accuracy of the translation on English idiomatic expression into Indonesian language in the film entitled “Tangled”. This study applies descriptive qualitative with the content analysis that uses textual and comparative analysis. The data source of this study is the film “Tangled” and its subtitle into the Indonesian language. The data collection procedures includes reading the source and the target text of the film script and excerpt the words, phrases, clauses, and sentences, then compare both to generate the data corpus. The data are then analyzed based on the accuracy of translation by Nababan. Based on the data analysis and discussion, it can be concluded that there are accurate, less accurate and inaccurate translation on idiomatic expressions in the “Tangled” film subtitle. From 115 idiomatic expressions found in the movie, 82 of them are categorized as accurate translations, 18 idioms are less accurate and 15 are inaccurate translation. From those findings, it can be stated that the translation on idiomatic expressions in the tangled movie is quite good.